"Not quenched" aggregates of a triphenylene derivative for the sensitive detection of trinitrotoluene in aqueous medium. (11th February 2016) - Arora, Harshveer; Pramanik, Subhamay; Kumar, Manoj; Bhalla, Vandana
Abstract : "Not quenched" porous aggregates of triphenylene derivative4 have been utilized for the detection of TNT in solution, solid and vapour phases with detection limits of 22.7 attograms cm −2 . Abstract : Triphenylene derivative4 bearing gallic acid groups at the periphery has been synthesized. Derivative4 formed "not quenched" porous aggregates in mixed aqueous medium. These aggregates served as potent chemosensors for the selective detection of trinitrotoluene (TNT) in mixed aqueous media and the detection limit in the range of 228.6 × 10 −12 g L −1 (228.6 parts per quadrillion) was observed. Interestingly, due to the porous morphology of these aggregates of derivative4, they could detect TNT in the vapor phase also. In addition, the dip strips coated by the aggregates of derivative4 could detect TNT in contact mode with detection limits of 22.7 attograms cm −2 .